From Plant Survival Under Severe Stress to Anti-Viral Human Defense – A Perspective That Calls for Common Efforts - Arnholdt-Schmitt, Birgit; Mohanapriya, Gunasekaran; Bharadwaj, Revuru; Noceda, Carlos; Macedo, Elisete Santos; Sathishkumar, Ramalingam; Gupta, Kapuganti Jagadis; Sircar, Debabrata; Kumar, Sarma Rajeev; Srivastava, Shivani; Adholeya, Alok; Thiers, KarineLeitão Lima; et al. (Frontiers in Immunology, 2021)
Reprogramming of primary virus-infected cells is the critical step that turns viral attacks harmful to humans by initiating super-spreading at cell, organism and population levels. To develop early anti-viral therapies and proactive administration, it is important to understand the very first steps of this process. Plant somatic embryogenesis (SE) is the earliest and most studied model for de novo programming upon severe stress that, in contrast to virus attacks, promotes individual cell and organism survival. We argued that transcript level profiles of target genes established from in vitro SE induction as reference compared to virus-induced profiles can identify differential virus traits that link to harmful reprogramming. To validate this hypothesis, we selected a standard set of genes named ‘ReprogVirus’. This approach was recently applied and published. It resulted in identifying ‘CoV-MAC-TED’, a complex trait that is promising to support combating SARS-CoV-2-induced cell reprogramming in primary infected nose and mouth cells. In this perspective, we aim to explain the rationale of our scientific approach. We are highlighting relevant background knowledge on SE, emphasize the role of alternative oxidase in plant reprogramming and resilience as a learning tool for designing human virus-defense strategies and, present the list of selected genes. As an outlook, we announce wider data collection in a ‘ReprogVirus Platform’ to support anti-viral strategy design through common efforts.